Optimizing Q-Learning for Automated Cavity Filter Tuning: Leveraging PCA and Neural Networks - Aghanim Amina; Otman Oulhaj; Oukaira Aziz; Lasri Rafik (EPJ Web of Conferences)
This paper presents a reinforcement learning-based approach to automate the tuning of a 6thorder combline bandpass filter, operating at 941 MHz, using a Q-learning algorithm. To reduce complexity, only two tuning screws are considered in the optimization. One of the main challenges in this process lies in the nonlinear relationship between screw positions and the filter’s frequency response, making conventional tuning methods difficult and inefficient. Additionally, while intelligent algorithms can assist in tuning, they often require large volumes of simulated data, leading to high computational costs. However, reducing the dataset size can compromise accuracy, as important frequency response information may be lost. To overcome these limitations, PCA is applied to minimize the dimensionality of the S11 response data, keeping only the most relevant information while improving computational efficiency. A feedforward neural network is employed to predict the PCA-reduced S-parameters, serving as a surrogate model that enables faster decision-making within the Q-learning framework. By integrating PCA at the data preprocessing stage, the number of frequency points is reduced from 401 to 20, significantly accelerating the Q-learning convergence process. The proposed approach, successfully reduces the tuning process from 1000 steps to just 45, ensuring faster and more precise optimization.